Kinetic and equilibrium adsorption study of anionic dyes using oil palm trunk-derived activated carbon. (2022) - Lim, Adeline; Chew, Jiuan Jing; Ismadji, Suryadi; Khaerudini, Deni Shidqi; Darsono, Nono; Sunarso, Jaka
Abstract: Oil palm trunk (OPT) was chemically activated to produce high surface area activated carbon (AC) in this work. The adsorption performances of OPT-derived AC in removing two different anionic dyes, i.e. acid blue 25 (AB 25) and sunset yellow (SY) from the aqueous solution, were evaluated individually and as a binary system. The effects of adsorbate concentration, pH, temperature, and duration were examined via batch adsorption studies. Both AB 25 and SY adsorption were most favourable at pH of 2, with the absence of electrostatic repulsion between AC and the dye components. The adsorption isotherm of AB 25 and SY can be well fitted using the non-linear Langmuir isotherm model, while the adsorption kinetics can be correlated well using the non-linear pseudo-second order model. The adsorption process of both anionic dyes was spontaneous and endothermic. The OPT-derived AC endured at least seven regeneration cycles during reusability tests with at least 80 % contaminant removal retained throughout.